A novel partitivirus confers dual contradictory effects to its host fungus: growth attenuation and virulence enhancement - Liu,Z; Chen,M; Kotta-Loizou,I; Coutts,RHA; Kong,L; Aboushedida,H; Sari,RK; Moriyama,H; Xu,W (Journal of Virology, 2025)
Mycoviruses possess a potential role for biological control due to their ability to reduce both virulence and vegetative growth in some phytopathogenic fungi. However, mycoviruses that enhance fungal pathogenicity have been poorly studied and characterized. In this study, a novel double-stranded RNA (dsRNA) fungal virus, tentatively named Sinodiscula camellicola partitivirus 1 (ScPV1), was identified in the phytopathogenic fungus Sinodiscula camellicola, isolated from tea leaves. ScPV1 possesses two genomic components of 1,835 bp and 1,697 bp in length, each containing an open reading frame (ORF) encoding a putative RNA-dependent RNA polymerase (RdRP) and coat protein (CP), respectively, as confirmed by mass spectrometry. Phylogenetic analysis of the amino acid sequences of the RdRPs from ScPV1 and related mycoviruses placed ScPV1 within a newly proposed genus, Epsilonpartitivirus, in the family Partitiviridae. The virus was purified using ultracentrifugation, and transmission electron microscopy revealed that ScPV1 dsRNA genomes are encapsidated in virus particles ca. 31 nm in size, ranging from 24.9 to 36.8 nm, together with the RdRP protein, which was of an unexpected size. Transfection with purified virions generated transfectants with significantly reduced growth rates but with increased virulence, indicating that ScPV1 confers unusual effects on its host fungus. This finding represents a significant advancement in understanding the complex interactions between mycoviruses and their host fungi.